PENGETAHUAN DAN KEPATUHAN PENDERITA DIABETES MELLITUS DALAM MELAKUKAN LATIHAN FISIK - Susanti Susanti (Adi Husada Nursing Journal, 2015)
Patients with Diabetes Mellitus is necessary therapeutic regimen for prevention or treatment, care to help patients to prevent complications. One is by providing information to physical activity to increase knowledge about the effects of Diabetes Mellitus patients and physical exercise. The purpose of this study was to determine the relationship of knowledge with diabetic patient compliance in physical exercise. The research method is a correlation with cross sectional approach, the research sample are 39 people with purposive sampling technique. The tools used assess knowledge and compliance of respondents using a questionnaire. Data collection is done coding, scoring, and tabulation and correlation test by Spearman Rank Test. The results showed that the results of the statistical test of Spearman rank correlation significance value (<0.05), it shows there is a relationship then H1 accepted which means that there is a relationship between knowledge and compliance of patients with Diabetes Mellitus in physical exercise. Results of this study can assist clients in improving the quality of life program Diabetes Mellitus patients through regular physical exercise. Suggested to the nurse to use the results of this study as a reference for improving services in diabetic patients leading to the needs of the patient in physical exercise. Penderita Diabetes Mellitus membutuhkan tindakan terapeutik untuk pencegahan atau penatalaksanaan, dan tindakan lain untuk mencegah komplikasi. Hal tersebut dapat dilakukan denga menambah informasi tentang aktifitas fisik untuk meningkatkan pengetahuan pasien Diabetes Mellitus. Tujuan penelitian ini untuk mengidentifikasi hubungan antara pengetahuan dengan kepatuhan penderita Diabetes Mellitus dalam melakukan latihan fisik. Metode penelitian menggunakan korelasi dengan pendekatan potong lintang. Sampel terdiri dari 39 responden dan menggunakan teknik purposive sampling. Pengukuran pengetahuan dan kepatuhan penderita Diabetes mellitus dalam melakukan latihan fisik menggunakan kuesioner. Data diolah menggunakan Spearman rank test. Hasil menunjukkan signifikan (<0,05). Hal ini menunjukkan terdapat hubungan antara pengetahuan dan kepatuhan penderita Diabetes Mellitus dalam melakukan latihan fisik. Hasil ini dapat menunjang penderita Diabetes Mellitus untuk meningkatkan kualitas hidup dan dapat digunakan sebagai sumber pustaka bagi perawat dalam meningkatkan pelayanan bagi penderita Diabetes Mellitus dalam melakukan latihan fisik. DOWNLOAD FULL TEXT PDF >>